2008
DOI: 10.1038/nrc2351
|View full text |Cite|
|
Sign up to set email alerts
|

Prostate-specific antigen and prostate cancer: prediction, detection and monitoring

Abstract: Testing for prostate-specific antigen (PSA) has profoundly affected the diagnosis and treatment of prostate cancer. PSA testing has enabled physicians to detect prostate tumours while they are still small, low-grade and localized. This very ability has, however, created controversy over whether we are now diagnosing and treating insignificant cancers. PSA testing has also transformed the monitoring of treatment response and detection of disease recurrence. Much current research is directed at establishing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
623
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 750 publications
(644 citation statements)
references
References 124 publications
10
623
1
10
Order By: Relevance
“…Unfortunately, current diagnostic and prognostic markers, including preoperative PSA levels and histological grade of the tumor, do not sufficiently distinguish those patients at risk of disease recurrence. 2 Therefore, it is of importance to find new molecular markers for better prognostic stratification of prostate cancer patients. Here, we show that a decrease or loss of SHP-1 expression correlates with a significantly decreased time to BCR and clinical progression, and multivariate analysis showed that SHP-1 remained an independent predictor when adjusted for preoperative PSA level, Gleason score and presence or absence of extra capsular extension, seminal vesicle invasion and positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, current diagnostic and prognostic markers, including preoperative PSA levels and histological grade of the tumor, do not sufficiently distinguish those patients at risk of disease recurrence. 2 Therefore, it is of importance to find new molecular markers for better prognostic stratification of prostate cancer patients. Here, we show that a decrease or loss of SHP-1 expression correlates with a significantly decreased time to BCR and clinical progression, and multivariate analysis showed that SHP-1 remained an independent predictor when adjusted for preoperative PSA level, Gleason score and presence or absence of extra capsular extension, seminal vesicle invasion and positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Radical prostatectomy (RP) serves as the first line of treatment for patients with localized prostate cancer. 2 However, in many cases the cancer will recur, as evidenced by rising levels of serum PSA, a phenomenon known as biochemical recurrence (BCR). This is an important concern and it is currently difficult to identify those patients at a high risk of tumor recurrence.…”
mentioning
confidence: 99%
“…1,2 Nonspecific binding and reproducibility remain problematic. 1,3,4 Typical immunoreagent selection criteria include affinity determination for an antibody−antigen interaction quantified by the equilibrium constant (K d ).…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…In the United States, the number of estimated new cases and deaths per year are 241 740 and 28 170, respectively (2). Screening with prostate-specific antigen (PSA) levels has led to an increased incidence of prostate cancer, but these "screening" cancers are generally smaller and of lower grade and stage than clinically detected cancers, leading to fears of overtreatment (3,4). The aim of active surveillance (AS) is to avoid radical treatment unless disease progression occurs or the individual with prostate cancer decides to undergo treatment.…”
Section: Study Design and Populationmentioning
confidence: 99%